Challenges and Ethical Considerations of Palliative Care in Indian Prisons - Barasker, Swapnil Kumar; Singhai, Pankaj; Nair, Maya; Kumar, Deepali (Journal of pain and symptom management, 2025)
Palliative care in Indian prisons faces challenges due to overcrowding, inadequate medical infrastructure, and societal neglect of incarcerated individuals. Chronic illnesses are common, yet regular follow-ups are lacking due to limited staff and resources. Psychological issues like mistrust in medical care and fear of dying alone further complicate care. Although medical parole exists, bureaucratic inefficiencies often lead to delayed or denied release. In contrast, few developed nations with prison hospice models integrate interdisciplinary teams and inmate caregivers, offering structured approaches to compassionate care despite facing challenges of their own. Ethical principles like autonomy, beneficence, nonmaleficence and justice are often compromised in Indian prisons, demanding policy reforms. Expanding hospice facilities, training prison staff in compassionate care, and improving the use of compassionate release mechanisms can ensure humane end of life care for incarcerated individuals.Palliative care in Indian prisons faces challenges due to overcrowding, inadequate medical infrastructure, and societal neglect of incarcerated individuals. Chronic illnesses are common, yet regular follow-ups are lacking due to limited staff and resources. Psychological issues like mistrust in medical care and fear of dying alone further complicate care. Although medical parole exists, bureaucratic inefficiencies often lead to delayed or denied release. In contrast, few developed nations with prison hospice models integrate interdisciplinary teams and inmate caregivers, offering structured approaches to compassionate care despite facing challenges of their own. Ethical principles like autonomy, beneficence, nonmaleficence and justice are often compromised in Indian prisons, demanding policy reforms. Expanding hospice facilities, training prison staff in compassionate care, and improving the use of compassionate release mechanisms can ensure humane end of life care for incarcerated individuals.